THE SOCIAL STRATIFICATION IN SNOWPIERCER MOVIE - Jurana, Jurana; Abdullah, Abdullah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
Social stratification is the classification of people into classes that can be arranged in stages. Social stratification can also be referred to as layers between communities that classify individuals and groups who have differences. Vertical hierarchical classification of society resulted in the emergence of social classes so that the terms upper social class, middle class, and lower class emerged. This research will examine (1) how social stratification is described in the snowpiercer movie and also (2) what is the impact of social class classification in the snowpiercer movie. The research method used in this study is the qualitative method. By using the snowpiercer movie as the main data used in research studies. Based on the results of the study it was concluded that 1) the picture of social stratification that occurs in the snowpiercer movie leads to the division of social classes based on the economic status of eternal train passengers. Where people who have money will enter as first-class passengers with an upper social class and live in luxury while those who do not have money will become occupants of the rear carriage with a low social class and live in hardship. 2) The impact of this social class division is the occurrence of conflict turmoil that occurs from the lower social classes against the upper social classes or often known as class struggle. The underclass as the oppressed who try to get a good life by carrying out a revolutionary movement as a form of protest against existing differences.Keyword: social stratification, social class